2022
DOI: 10.3390/ijms23094603
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Molecular Regulation of Lignin Content in Triploid Poplar Leaves

Abstract: After polyploidization, plants usually undergo some morphological and physiological changes, including the lignin content of polyploids usually becoming lower than that of diploids. However, the regulatory mechanism of the variation of lignin content in polyploid plants remains unclear. Therefore, in this research, we used full-sib poplar triploids and diploids to explore the molecular regulatory basis of lignin content in poplar triploid leaves through the determination of lignin content, the observation of x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Our findings indicate that the lignin content of tetraploids P. hopeiensis was significantly lower than that of their diploid counterparts. This suggests that gene dosage effects might increase the size of cells and organelles by altering gene expression, and this is usually accompanied by a decrease in cell surface area per unit volume, which might reduce lignin accumulation [ 18 ]. We also found that the cell wall thickness of tetraploids was significantly higher than that of diploids, indicating that the reduction in the lignin content in the cell wall might be compensated for by another cell wall polymer or matrix polysaccharide, such as cellulose, hemicellulose, and pectin [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that the lignin content of tetraploids P. hopeiensis was significantly lower than that of their diploid counterparts. This suggests that gene dosage effects might increase the size of cells and organelles by altering gene expression, and this is usually accompanied by a decrease in cell surface area per unit volume, which might reduce lignin accumulation [ 18 ]. We also found that the cell wall thickness of tetraploids was significantly higher than that of diploids, indicating that the reduction in the lignin content in the cell wall might be compensated for by another cell wall polymer or matrix polysaccharide, such as cellulose, hemicellulose, and pectin [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, triploid clones showed higher averages of LL, LA, P n , and WUE , which was the same result as in other research. This may indicate that plants with an increased number of chromosomes may cause some morphological changes by influencing various physiological activities and metabolic processes [ 49 ]. However, the Pn and WUE values of the triploid were higher than those of the diploid and tetraploid; these results were the same as those of research on hybrid poplar clones [ 26 ], but in P. ussuriensis , triploid is the largest, diploid is the smallest, and tetraploid is the center [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flavonoid content was expressed as mg g −1 sample. The lignin content was determined by spectrophotometry according to the method of Xu et al 27 . Acetyl lignin is produced after the phenol hydroxyl in lignin is acetylated.…”
Section: Methodsmentioning
confidence: 99%